Supplementary Feeding of Goats during Transition Period: A Participatory Action Research in North-Eastern Transition Zone of Karnataka State, India - Rathod, Prakashkumar; Veeranna, K. C.; Ramachandra, B.; Biradar , Channappagouda; Desai, Anant Rao (International Journal of Livestock Research, 2018)
Supplementary feeding of goats during transition period is the major drive for improving the productivity through reproductive performance of goats. In this context, a participatory action oriented approach was followed in purposively selected Karnataka Watershed Development Department (KWDP)-Sujala-III project villages since this project is implemented in this district by Veterinary College, Bidar. About 220 goat rearing households were contacted for this activity, out of which a total of 96 does from 16 respondents were selected with same stage of pregnancy and body condition score. The project clearly revealed that an integrated approach of extension activities viz. training, demonstration, on-farm testing, farm literature etc. has achieved the expected target and has convincingly demonstrated the importance of supplementary feeding of goats during transition period. There is an increase in income generation through improved kidding percentage, kid birth weight, kid growth, doe health condition, multiple births etc. Further, the authors have observed decrease in economic losses due to kid mortality and problems during kidding. The project has also witnessed the convergence of multi-stakeholders for achieving a common objective of improving productivity and hence, this experience of convergence can be applied at a larger scale.